The daily arterial stiffness profile in rheumatoid arthritis patients with and without hypertension - N. M. Nikitina; T. A. Romanova; A. P. Rebrov (Современная ревматология, 2017)
Patients with rheumatoid arthritis (RA) have an increased risk for cardiovascular diseases. To determine their daily arterial stiffness (AS) as an indicator of cardiovascular risk is of unquestionable interest.Objective: to evaluate the features of daily AS in RA patients with or without hypertension.Patients and methods. Twenty-four hour AS monitoring (24-h ASM) was done in 75 women with a valid diagnosis of RA. The patients were randomized into 3 groups: 1) 39 RA patients with hypertension; 2) 24 RA patients without hypertension; 3) 12 RA patients with masked hypertension. A comparison group consisted of 30 hypertensive patients without RA and a control group included 22 apparently healthy women who were age-matched with the patients with RA and those from the comparison group. 24-h ASM readings were studied using a BPlab device with Vasotens software (Russia).Results. All the patients with RA were found to have higher 24-h ASM readings than the controls; and, in the presence of hypertension, these changes were even more pronounced. Group 1 was noted to have higher ambulatory AS index than the comparison group; more than 70% of the patients in Group 2 were observed tohave increased aortic pulse wave velocity when reducing to a blood pressure (BP) of 100 mm Hg. The patients in Groups 1 and 2 had increases in augmentation index, in the latter normalized for a heart rate of 75 beats/min, in the propagation time of a reflected wave when reducing to a BP of 100 mm Hg, and in AS index at night. The patients with RA showed an association between daily AS and major cardiovascular risk factors (hypertension, age, body mass index, menopause duration), RA-specific risk factors (RA duration, erythrocyte sedimentation rate, and C-reactive protein), and psychoemotional status. Conclusion. 24-h ASM revealed that the patients with RA had higher vascular wall stiffness than the individuals in the comparison and control groups. Taking into consideration the pronounced changes in AS not only during the daytime, but also during the night, it is appropriate to perform daily monitoring in patients with RA in order to obtain more objective data.